Moral Distress Among Oncology Social Workers. Issue 7 (July 2021) - Guan, Ting; Nelson, Krista; Otis-Green, Shirley; Rayton, Makeeta; Schapmire, Tara; Wiener, Lori; Zebrack, Brad
Abstract : PURPOSE: Literature on moral distress among oncology social workers (OSWs) is sparse. The aim of the current study was to examine the prevalence of moral distress and its domains of influence, and to identify demographic and work-related characteristics associated with moral distress among OSWs. METHODS: Data came from the Oncology Social Work Competencies, Opportunities, Roles, and Expertise survey, conducted from August to September 2020 (during the COVID-19 global pandemic). Data collected included demographic information (eg, age, sex, and race) and work-related characteristics (eg, job position, organization type, work setting, employment status, salary, years in the profession, and OSW-C certification). Moral distress was measured using the Measure of Moral Distress for Healthcare Professionals. Tests of association, including multivariate linear regression, were conducted to achieve the research aims. RESULTS: Total moral distress scores on the Measure of Moral Distress for Healthcare Professionals (range 0-432) for 745 OSWs ranged from 1 to 273, with an average score of 74.0. The three highest indicators of moral distress were observed in the patient or family experience domain. Higher levels of moral distress were associated with younger age, being a direct service provider, provision of inpatient cancer care, and more years in the profession. CONCLUSION: OSWs are experiencing moral distress. Institutional investments in professional education and support of OSWs are needed to mitigate and possibly prevent moral distress experienced by cancer care providers and thus ensure the delivery of quality psychosocial care for patients with cancer and their families.